A disciplina de língua portuguesa para o ciclo I do ensino fundamental da secretaria estadual de educação de São Paulo - Souza, Sheila Moreschi Campos de (2014)
This research has as its central theme the Unified Curriculum Proposal implanted linearly by the Secretary of Education of the São Paulo State in the state system of Basic Education at the beginning of the year 2008. Our object is the discipline of Portuguese Language for the Cycle I of the Elementary School. Considering the objectives of this proposal seeks to understand by means of the speech of teachers in the early years of elementary education as they have appropriated the proposal in the course of school practice, what they think about the offer of didactic-pedagogical resources to schools and how they articulate their changes of this subject with the debate on quality in education. The primary sources of research are constituted of documents that guide the curriculum for the early grades and semi-structured interviews with teachers. In the teachers' responses the majority of them show sensitive to curriculum proposal differing only by the higher incidence of certain elements pointed out on the changes and the degree of importance attributed to them. It might also be noticed that the changes introduced in the curriculum guidelines are appropriate in everyday life and in the practice of teachers. Through the interviews it was possible to verify that giving voice to the teachers to expose the school routine creates conditions that can help in the development of critical thinking on educational policies and the improvement of their working condition.